Indeks Kepuasan Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Sultan Ageng Tirtayasa - Ika Utami Widyaningsih; H Djasuro Suryo (Jurnal Ilmiah Poli Bisnis, 2020)
Improving the quality of higher education (college) services is a determining factor in increasing student satisfaction. This study aims to measure the index of student satisfaction with the service units at FEB Untirta in the hope that it can be a consideration for faculty leaders to make policy improvements in the future. The research method used a survey method through a questionnaire distributed to 150 students who became research respondents. The service elements studied to measure the satisfaction index used the provisions of the elements of public services contained in the KepMenPAN 2004. The results indicated that the 14 elements of the service index in FEB Untirta consisted of: service procedures, service requirements, clarity of service officers, service officer discipline, responsibility of service officers, ability of service officers, speed of service, justice in getting services, politeness and friendliness of officers, fairness of service fees, certainty of service fees, certainty of service schedules, environmental comfort and service safety; all in good category.